Measurement of Mathematical Literacy in Everyday Life Context: A Case Study on High School Students Reviewed by Gender - Aulia, Hartika; Mandailina, Vera; Mahsup, Mahsup; Syaharuddin, Syaharuddin; Rini, Widia; Sahraini, Alfiana (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2024)
This research aims to measure the level of mathematical literacy in the context of daily life among high school students, with a focus on differences between male and female students. The research method employed is quantitative with a survey approach. A total of 13 male students and 24 female students from various high schools participated as subjects. The instrument used was a Likert scale questionnaire consisting of 15 statements designed to measure students' perceptions and understanding of mathematical literacy in everyday life. Data analysis was conducted using the paired sample t-test to compare differences in responses between male and female students. The analysis results showed a paired sample t-test value of -0.368, with a significance value (sig) of 0.719. These findings indicate that there is no significant difference between the responses of male and female students regarding mathematical literacy in the context of daily life. Nevertheless, this research provides an important contribution to understanding students' perceptions of mathematical literacy and its implications in the educational context. Further research can delve into the factors influencing students' perceptions of mathematical literacy and broaden the sample scope to obtain a more holistic understanding of the phenomena under investigation.